Kajian Risiko Kesehatan Terkait Pajanan Benzene, Toluene dan Xylene pada Pekerja Kilang Minyak PT. X - Halizah, Putri Noer; Tejamaya, Mila (National Journal of Occupational Health and Safety, 2024)
Workers in oil and gas production units are at risk of exposure to chemical hazards. One of the ingredients in petroleum is volatile organic compounds (VOC), with examples of ingredients known for their toxicity being benzene, toluene and xylene. This study aims to assess health risks related to exposure to benzene, toluene and xylene of oil refinery workers at PT. X. This study will analyze personal exposure to inhalation routes from benzene, toluene and xylene chemicals using the Chemical Health Risk Assessment (CHRA) method from the Department of Safety and Health, Malaysia. The study results showed that the risk level from benzene was very high, while the risk level from toluene and xylene was at a moderate level. The highest exposure to benzene, toluene and xylene is in distillation units. Based on the results of the study, appropriate controls are needed to overcome exposure to benzene, toluene and xylene. One of the controls that can be done is to improve the ventilation system and tighten the use of personal protective equipment. Keywords: refinery unit, health risk assessment, benzene, toluene, xylene.